Natural Decay Resistance of Acacia auriculiformis Cunn. ex. Benth and Dalbergia sissoo Roxb (Bangladesh Journal of Scientific and Industrial Research, 2011)
Natural decay resistance of two fast growing timber species, Acacia auriculiformis Cunn. ex. Benth. and Dalbergia sissoo Roxb. grown in Bangladesh was evaluated by adopting an accelerated decay test method. The wood specimens were exposed to a white rot fungus, Schizophyllum communie for 12 weeks. The natural decay resistance was determined by the weight loss percentage of the tested wood specimens. The weight losses were found 2.0% and 4.37% in heartwood, and 22.19% and 13.61% in sapwood of A. auriculiformis and D. sissoo, respectively. In both the species, the weight loss was significantly higher in sapwood than heartwood. This means that heartwood was more resistant than sapwood. The weight loss significantly increased from bottom to top. Significant variation has been observed in weight loss between A. auriculiformis and D. sissoo both in heartwood and sapwood. The wood of A. auriculiformis and D. sissoo were classified as naturally durable following the standard classification of natural durability. Key words: Decay resistance; Acacia auriculiformis; Dalbergia sissoo; Schizophyllum communie; Accelerated decay test DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8189 Bangladesh J. Sci. Ind. Res. 46(2), 225-230, 2011